The Global Business of Sport in a Brave New World: Conceptualising a Framework for Alternative Futures - Jackson, Steven J.; Dawson, Marcelle C. (Frontiers in Sports and Active Living, 2021)
In July 1991, Sports Illustrated published a special issue featuring two articles that prognosticated about what sport would look like 10 years later. As the world entered the 21st century, Sports Illustrated writers, Oscar Johnson and Ron Fimrite, offered their visions of sport in the year 2001. Their analysis highlighted how a range of economic, social and technological changes in society would impact on how sport is structured, produced and consumed, but also offered insights into the future of the major professional sport leagues in North America. It has been 30 years since they publicised their views and, while technology continues to impact sport, the Covid-19 pandemic has forced the world to pause and to consider a range of deep, soul-searching questions about the nature of society, including sport. Against this background, we consider the opportunities and challenges for sport in the 21st century. The paper is divided into three sections including: (1) a reflection on the meaning, value and significance of sport including its privileged position in society, or what we refer to as “sporting exceptionalism”; (2) a brief overview of a case study that illustrates the challenges facing the global business of sport; and, (3) a framework for conceptualising alternative futures in the global business of sport, drawing on examples from women's sport.